Sharing of Snorting Straws and Hepatitis C Virus Infection in Pregnant Women. Issue 2 (August 2016) - Fernandez, Noelle; Towers, Craig V.; Wolfe, Lynlee; Hennessy, Mark D.; Weitz, Beth; Porter, Stephanie
Abstract : OBJECTIVE: To evaluate possible modes of hepatitis C virus (HCV) acquisition in pregnant women found to be HCV-infected in the prenatal period and to assess transmission risk factors. METHODS: This was a prospective cohort study conducted from March 2014 through June 2015 involving the distribution of an anonymous survey to HCV-infected pregnant women that assessed for numerous modes of potential HCV transmission involving, intravenous drug use, blood transfusion, organ transplant, sexual contact, tattoos, and snorting drugs with a straw. Participants were drawn from our institutional obstetric high-risk clinic. Statistical analysis involved simple percentages and χ 2 comparisons where appropriate; P <.05 was considered significant. To test biologic plausibility, snorting utensils confiscated by law enforcement authorities from patients not in this study were tested for the presence of human blood. RESULTS: A total of 189 HCV-infected pregnant patients completed the survey, and no approached patients declined. Of these, 136 (72%, 95% confidence interval [CI] 65–78%) admitted to intravenous drug use, of whom 89 (65%, 95% CI 57–73%) reported sharing needles. Of the 178 (94%, 95% CI 90–97%) who admitted snorting drugs, 164 (92%, 95% CI 87–96%) reported sharing straws. The difference between the proportion reporting sharing of snorting utensils compared with the proportion sharing intravenous drug use utensils was significant ( P <.001). Twenty-nine patients (15%, 95% CI 11–21%) reported snorting drugs and sharing straws but denied any other risk factor except sexual contact. Of the 54 straws confiscated by law enforcement authorities, 13 (24%, 95% CI 13–38%) tested positive for the presence of human blood. CONCLUSION: Sharing snorting utensils (straws) in noninjection drug use may be an additional risk factor for HCV and other virus transmission. Abstract : The sharing of snorting utensils when abusing illicit drugs could risk transmitting hepatitis C and other bloodborne viruses.